Sodium battery positive electrode material and preparation method and application thereof

By controlling the XRD structural characteristics of sodium-based transition metal oxides and making their inactive crystal surface optimal orientation, the problems of layered sodium-based transition metal oxides in air and circulation stability are solved, and the air and circulation stability of the material are achieved Improved performance, improving the battery's circulation performance and energy density.

CN119447205APending Publication Date: 2025-02-14HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310961628.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Laminated sodium-based transition metal oxides have problems with air and circulation stability, resulting in unstable in the air environment containing water and CO2, and create cracks during the circulation, affecting electrochemical properties.

Method used

By controlling the XRD structural characteristics of the sodium-based transition metal oxide, the inactive crystal surface (003) is preferred, thereby improving the air and circulation stability of the material. The specific implementation method includes adjusting the diffraction peak intensity ratio of the (003) crystal plane to the (012) and (110) crystal planes to ensure that it is in the range of 2.7-6.0 and 4.0-8.0, respectively, in the form of single-crystal particles and polycrystal particles. There are and a cladding is added in some embodiments to further enhance stability.

Benefits of technology

It effectively improves the air stability and cyclic stability of the sodium-electrode material, avoids interfacial side reactions caused by cracks, improves the structural stability and sodium ion transport performance of the material, and thus improves the cyclic performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447205A_ABST
    Figure CN119447205A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a sodium battery positive electrode material and a preparation method and application thereof. The sodium battery positive electrode material comprises a sodium-based transition metal oxide, and the XRD spectrogram of the sodium-based transition metal oxide satisfies the following conditions: the ratio of the diffraction peak intensity of the crystal face (003) to the diffraction peak intensity of the crystal face (012) is greater than or equal to 2.7, and / or the ratio of the diffraction peak intensity of the crystal face (003) to the diffraction peak intensity of the crystal face (110) is greater than or equal to 4.0. When the XRD spectrogram of the sodium battery positive electrode material meets the above conditions, it can be ensured that the non-active crystal face (003) has preferred orientation, and it can be fundamentally ensured that the air stability and the cycle stability of the material are synchronously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of sodium ion batteries, and specifically to a sodium battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Since sodium resources are abundant and cheap on Earth, sodium-ion batteries have low production costs and no over-discharge problems, and have become one of the research hotspots in the field of secondary batteries. Layered sodium-based transition metal oxides with high specific capacity are commonly used positive electrode active materials for sodium-ion batteries, but poor air stability and cycle stability are the two major pain points of this type of material.

[0003] The poor air stability of the above materials is mainly due to the fact that when they are exposed to air containing water and CO2, the Na + It is easy to escape and generate alkaline substances on the surface of the material. The presence of alkaline substances on the surface will increase the surface impedance of the material, reduce its capacity, and increase the stability and coating effect of the subsequently prepared positive electrode slurry; water / CO2 in the air will also be embedded along the active surface of the material, causing microstructural defects such as cracks, affecting the capacity. The poor cycle stability of the above materials is mainly due to the multi-level phase changes and stress accumulation during the cycle process, which lead to defects such as cracks along the active surface, and the generation of cracks will lead to more interfacial side reactions, which will deteriorate the cycle stability. Therefore, the air / cycle stability of the above materials is closely related to the intrinsic structure of the material.

[0004] There are reports in the industry that the air stability is improved by pickling or surface coating, but pickling can only reduce the initial residual alkali on the surface of the material. After the material is left alone, residual alkali continues to be generated, and it is impossible to form a long-term barrier protection. Pickling inevitably causes the dissolution of sodium ions in the bulk phase, resulting in a decrease in specific capacity and deterioration of cycle performance. The coating amount of the surface is limited, and the air stability / interface stability of the uncoated area is still poor. Moreover, coating cannot fundamentally reduce the generation of cracks and improve the cycle stability of the material. Therefore, it is necessary to provide a technical solution that can effectively improve the air and cycle stability of layered sodium-based transition metal oxides at the same time. Summary of the invention

[0005] In view of this, the present application is based on the root cause of the air / cycle stability failure of sodium-based transition metal oxides, and provides a sodium battery positive electrode material and its preparation and application. By controlling the XRD structural characteristics of layered sodium-based transition metal oxides, the inactive crystal planes are preferentially oriented, thereby fundamentally ensuring that the air stability and cycle stability of the material are improved simultaneously.

[0006] In a first aspect, an embodiment of the present application provides a sodium positive electrode material, which includes a sodium-based transition metal oxide, and the X-ray diffraction spectrum of the sodium positive electrode material satisfies: the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and / or the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.0.

[0007] When the XRD spectrum of the sodium cathode material meets the above conditions, it can be reflected that its inactive crystal face (003) has a preferential orientation and the crystal face is exposed more, which helps to inhibit the embedding of H2O and CO2 in the air into the sodium-based transition metal oxide along the (012) and / or (110) active faces, and inhibit the Na + It escapes along the active surface and reacts with H2O / CO2 in the air, thus ensuring the good air stability of the sodium-based transition metal oxide; at the same time, it also helps to suppress the problem of more interfacial side reactions caused by cracks along the active surface, and improve its cycle stability.

[0008] In some embodiments of the present application, the ratio of the diffraction peak intensity of the (012) crystal plane to the (110) crystal plane is in the range of 1 to 3. This can further improve the air stability and cycle stability of the material, and help to suppress the problem of affecting the electrochemical performance of the material due to the generation of transition metal oxide impurity phases due to excessive exposure of the (110) crystal plane.

[0009] In some embodiments of the present application, the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is in the range of 2.7-6.0. In this case, the air stability and cycle stability of the above-mentioned sodium positive electrode material are both high, and the problem of decreased sodium ion transport kinetics of the material caused by excessive orientation of the (003) crystal plane is avoided.

[0010] In some embodiments of the present application, the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is in the range of 4.0-8.0. In this case, the air stability and cycle stability of the above-mentioned sodium positive electrode material are both high, and the problem of decreased sodium ion transport kinetics of the material caused by excessive orientation of the (003) crystal plane is avoided.

[0011] In an embodiment of the present application, the sodium-based transition metal oxide includes single crystal particles and / or polycrystalline particles; wherein the single crystal particles are primary particles, and the polycrystalline particles are secondary particles composed of a plurality of the primary particles.

[0012] In the embodiment of the present application, the primary particles are hexagonal flaky particles, and the ratio of the length to the thickness of the primary particles is in the range of 1.5 to 8. This is more conducive to the exposure of the inactive (003) crystal plane of the sodium-based transition metal oxide, and ensures that its air and cycle stability are improved, and avoids the problem of decreased sodium ion transport kinetics of the material caused by excessive orientation of the (003) crystal plane.

[0013] In the embodiment of the present application, the thickness of the primary particles is in the range of 0.04 μm to 6 μm, which is conducive to ensuring that the sodium-based transition metal oxide has both good structural stability and sodium ion transport performance.

[0014] In some embodiments of the present application, the D50 particle size of the single crystal particles is in the range of 0.5 μm-12 μm, and the D99 particle size does not exceed 30 μm. The sodium-based transition metal oxide with a single crystal structure has a suitable D50 particle size, which is conducive to ensuring that the single crystal particles have both a shorter sodium ion diffusion path and a higher compaction density; the D99 of the single crystal particles is in the above range, which can ensure that the single crystal particles have good dispersibility and avoid excessive agglomeration of primary particles.

[0015] In some embodiments of the present application, the D50 particle size of the polycrystalline particles is in the range of 1 μm-15 μm, and the D99 particle size is not more than 30 μm. The polycrystalline sodium-based transition metal oxide has a suitable D50 particle size, which can ensure that its structural stability is high, the interface side reaction is small, and the rate performance is good; the D99 of the polycrystalline particles is in the above range, which can also avoid the presence of polycrystalline particles with too large particle size and deterioration of its rate performance.

[0016] In the embodiment of the present application, the chemical formula of the sodium-based transition metal oxide includes Na x A y M z O w , wherein A is a variable valence transition metal element, and M is selected from one or more of Li, Al, Mg, Ca, Sr, K, Sn, Ti, Zn, Zr, Nb, Mo, and B; <x≤12,0<y≤12,0≤z≤12,0<w≤12。

[0017] In some embodiments of the present application, the sodium positive electrode material further includes a coating layer coated on the surface of the sodium-based transition metal oxide; wherein the material of the coating layer includes one or more of oxides, fluorides, and phosphates. The presence of the coating layer can further improve the air stability and cycle stability of the sodium positive electrode material.

[0018] In the embodiment of the present application, the coating layer has a thickness of 0.1 nm to 100 nm. A coating layer of suitable thickness can effectively improve the air stability and cycle stability of the sodium positive electrode material while not affecting the specific capacity of the material due to the excessive thickness of the coating layer.

[0019] In the embodiment of the present application, the compaction density of the sodium positive electrode material at 200 MPa is 2.6-3.5 g / cm 3 , with a specific surface area of ​​0.2-1.5m 2 / g. The sodium battery cathode material has the above XRD characteristics and the morphology and size characteristics of the primary particles, which can make the compaction density and specific surface area of ​​the sodium battery cathode material reach this condition, thereby facilitating the sodium battery made of the material to have both good cycle stability and high energy density.

[0020] A second aspect of an embodiment of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, and the positive electrode active material layer includes the sodium battery composite positive electrode material described in the first aspect of the embodiment of the present application.

[0021] The sodium secondary battery made with the positive electrode sheet has good cycle stability. In addition, since the compaction density of the sodium positive electrode material is relatively high, the compaction density of the positive electrode sheet can also be relatively high, and the specific capacity of the sodium secondary battery can be relatively high.

[0022] The third aspect of the embodiment of the present application provides a sodium secondary battery, comprising the positive electrode sheet and the negative electrode sheet as described in the second aspect of the embodiment of the present application. The sodium secondary battery has good cycle performance and high specific capacity characteristics.

[0023] The fourth aspect of the embodiment of the present application provides an electric device, which includes the sodium secondary battery described in the third aspect of the present application. The electric device includes one or more of an electronic device and a mobile device.

[0024] By using the sodium secondary battery provided in the embodiment of the present application to power the electrical equipment, the user experience and market competitiveness of the product can be improved.

[0025] The fifth aspect of the embodiment of the present application provides an energy storage system, the energy storage system comprising a plurality of sodium secondary batteries as described in the third aspect of the embodiment of the present application. The sodium secondary batteries used in the energy storage system have good cycle stability.

[0026] The present application also provides a method for preparing the above-mentioned sodium positive electrode material, comprising the following steps:

[0027] (1) mixing a sodium source with other element sources in the sodium-based transition metal oxide to be prepared to obtain a mixed dry material;

[0028] (2) sintering the mixed dry material multiple times to obtain a sodium-based transition metal oxide-containing sodium positive electrode material; wherein, in the multiple sinterings, the holding temperature of each sintering is within the range of 800-1200° C., and the sintered material obtained by each sintering is crushed before the next sintering, so that the X-ray diffraction spectrum of the sodium positive electrode material satisfies: the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and / or the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.0.

[0029] The preparation method has simple process and is easy to operate, and can produce a sodium battery positive electrode material having the above-mentioned XRD spectrum characteristics of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1A , Figure 1B , Figure 1C Several structural schematic diagrams of the sodium battery positive electrode material 100 provided in the embodiments of the present application.

[0031] Figure 2 A schematic diagram of the structure of the positive electrode plate provided in an embodiment of the present application.

[0032] Figure 3 This is a schematic diagram of the structure of a sodium secondary battery provided in an embodiment of the present application.

[0033] Figure 4 A schematic diagram of the structure of an electronic device provided in an embodiment of the present application.

[0034] Figure 5 A schematic diagram of the structure of the energy storage system provided in an embodiment of the present application.

[0035] Figure 6 The X-ray diffraction (XRD) spectra of the sodium cathode materials prepared in Example 1 and Comparative Example 1 are summarized.

[0036] Figure 7 This is an electron microscope photograph of the sodium positive electrode material of Example 1.

[0037] Figure 8 This is the XRD spectrum of the sodium battery positive electrode material prepared in Example 2.

[0038] Fig. 9 This is a scanning electron microscope photograph of the sodium positive electrode material prepared in Example 2. DETAILED DESCRIPTION

[0039] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0040] In view of the problem that existing sodium-based transition metal oxides are prone to air / cycle stability failure and cannot be effectively solved, an embodiment of the present application provides a sodium battery positive electrode material.

[0041] Specifically, if Figure 1A As shown, the sodium positive electrode material 100 provided in the embodiment of the present application includes a sodium-based transition metal oxide 10, and the XRD spectrum of the sodium positive electrode material 100 satisfies: the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and / or the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.0. Among them, the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane specifically refers to the ratio of the peak intensity (i.e., peak height) of the diffraction peak corresponding to the (003) crystal plane to the peak intensity (i.e., peak height) of the diffraction peak corresponding to the (012) crystal plane. The ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane specifically refers to the ratio of the peak intensity (i.e., peak height) of the diffraction peak corresponding to the (003) crystal plane to the peak intensity (i.e., peak height) of the diffraction peak corresponding to the (110) crystal plane.

[0042] When the XRD spectrum of the sodium-based cathode material 100 meets the above conditions, it can be reflected that the sodium-based cathode material 100 has a (003) crystal plane preferential orientation, and the (003) crystal plane is correspondingly more exposed; and the (003) crystal plane is a low-activity surface (or "inactive surface") of the sodium-based transition metal oxide, and the (012) crystal plane and the (110) crystal plane are high-activity surfaces of the sodium-based transition metal oxide, and the (003) inactive crystal plane has good air stability, and its preferential orientation / full exposure helps to inhibit H2O and CO2 in the air from being embedded in the sodium-based transition metal oxide along the active surface - (012) crystal plane and / or (110) crystal plane, thereby inhibiting Na + The sodium positive electrode material 100 is good in air stability. In addition, during the cycle of the positive electrode material, cracks are mostly generated along the active surface, and the preferred orientation of the (003) inactive crystal plane is also conducive to inhibiting the generation of cracks, improving the structural stability of the material, inhibiting the occurrence of more interface side reactions caused by the generation of cracks, improving the cycle stability, and facilitating the capacity. Therefore, the sodium positive electrode material that meets the above XRD spectrum conditions can take into account both good air stability and cycle stability.

[0043] In some embodiments of the present application, the XRD spectrum of the sodium positive electrode material 100 satisfies the following conditions at the same time: the diffraction peak intensity ratio of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and the diffraction peak intensity ratio of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.0. In this case, it is shown that the active planes (012) and (110) in the sodium-based transition metal oxide are simultaneously suppressed by the preferentially oriented (003) crystal plane, and the air stability and cycle stability thereof are improved to a high degree.

[0044] In the embodiment of the present application, the ratio of the diffraction peak intensity of the (012) crystal plane and the (110) crystal plane of the sodium positive electrode material 100 (i.e., I (012) / I (110) ) is in the range of greater than or equal to 1.0 to less than or equal to 3.0 (i.e., in the range of 1.0-3.0). (012) / I (110) Less than 3 can reflect that the highly active (012) crystal plane is further suppressed, which is more conducive to improving the air stability and cycle stability of the material. In addition, compared with the (012) crystal plane, the (110) crystal plane is prone to the aggregation of transition metal elements such as Ni, producing transition metal oxide impurity phases (such as NiO impurity phases), thereby weakening the electrochemical performance of the material. (012) >I (110) The problem of NiO impurity phase caused by excessive exposure of the (110) crystal plane can be reduced. In some embodiments, the ratio of the diffraction peak intensity of the (012) crystal plane to the (110) crystal plane is 1.0-2.67, for example, specifically 1.1, 1.2, 1.3, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or 2.6, etc. Further, the ratio of the diffraction peak intensity of the (012) crystal plane to the (110) crystal plane is in the range of 1.4-2.3.

[0045] In some embodiments of the present application, the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane of the sodium positive electrode material 100 (i.e., I (003) / I (012)) is in the range of 2.7-6.0; for example, specifically 2.71, 2.75, 2.8, 2.9, 2.95, 3.0, 3.01, 3.02, 3.05, 3.10, 3.15, 3.20, 3.3, 3.4, 3.5, 4.0, 4.2, 4.5, 5.0, 5.5, 5.8, 5.9, 6.0, etc. In some embodiments, the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is 2.71-5.0. In some embodiments, when the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is 3.0-5.0, the air stability and cycle stability of the sodium positive electrode material 100 are both high, and the problem of decreased sodium ion transport kinetics of the material caused by excessive orientation of the (003) crystal plane is avoided. Further, the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane may be 3.01-4.0.

[0046] In some embodiments of the present application, the ratio of the diffraction peak intensity of the (003) crystal plane and the (110) crystal plane of the sodium positive electrode material 100 (i.e., I (003) / I (110) ) is in the range of 4.0-8.0; for example, 4.01, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.05, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.2, 7.5, 7.8, 7.9, 8.0, etc. In some embodiments, the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is in the range of 4.1-7.0. When the ratio is 4.1-7.0, the air stability and cycle stability of the sodium positive electrode material 100 are both high, and the problem of decreased sodium ion transport kinetics of the material caused by excessive orientation of the (003) crystal plane is avoided. In other embodiments, the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is in the range of 4.2-6.5.

[0047] It should be noted that, when the sodium-based cathode material 100 only includes sodium-based transition metal oxide, the XRD spectrum characteristics of the above-mentioned sodium-based cathode material 100 are the XRD spectrum characteristics of the sodium-based transition metal oxide.

[0048] In the embodiment of the present application, the primary particles of the sodium-based transition metal oxide are hexagonal flaky particles, and the ratio of the length to thickness of the primary particles is in the range of 1.5-8.0. Among them, the morphology of the primary particles is hexagonal flaky, which is more conducive to exposing the inactive (003) crystal plane, so that the XRD spectrum of the above-mentioned sodium positive electrode material can better meet the above requirements. The crystal planes corresponding to the upper and lower planes of the hexagonal flaky particles are inactive (003) crystal planes, and the crystal planes corresponding to the side surfaces of the hexagonal particles include at least one of the (012) crystal plane and the (110) crystal plane. In addition, the ratio of the length to thickness of the primary particles is controlled in the range of 1.5-8.0, which not only helps to ensure that the sodium-based transition metal oxide is a crystalline material with a preferential orientation of the (003) crystal plane, and ensures that its air and cycle stability are improved, but also avoids the problem of decreased sodium ion transport kinetics of the material caused by excessive orientation of the (003) crystal plane. Specifically, the ratio of the length to the thickness of the primary particles can be 2.0, 2.2, 2.5, 2.8, 3.0, 3.5, 4.0, 4.2, 4.5, 4.8, 5.0, 6.0, 7.0, 7.5, etc.; in some embodiments, the ratio of the length to the thickness of the primary particles is in the range of 2.5-5.

[0049] In the embodiment of the present application, the length of the primary particle is in the range of 0.5 μm-12 μm. The thickness of the primary particle is in the range of 0.04 μm-6 μm. The length and thickness of the primary particle are in an appropriate range, which is conducive to ensuring that the sodium-based transition metal oxide has good structural stability and sodium ion transport performance. Specifically, the length of the primary particle is, for example, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 11.5 μm, etc. The thickness of the primary particles is, for example, 0.05 μm, 0.08 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6.0 μm, etc. In some embodiments, the thickness of the primary particles is in the range of 0.05 μm-3 μm.

[0050] In an embodiment of the present application, the sodium-based transition metal oxide may include single crystal particles and / or polycrystalline particles. The single crystal particles are the above-mentioned primary particles. The polycrystalline particles are secondary particles composed of a plurality of the primary particles, that is, the polycrystalline particles are a collection of a plurality of single crystal particles. In an embodiment of the present application, the morphology of the polycrystalline particles includes one or more of spherical, ellipsoidal, and flower-like shapes, but is not limited thereto.

[0051] In the embodiment of the present application, the D50 particle size of the single crystal particles is in the range of 0.5 μm-12 μm, and the D99 particle size does not exceed 30 μm.

[0052] Since the single crystal particles are primary particles, the D50 particle size of the single crystal particles is similar to the length range of the primary particles mentioned above. Controlling the D50 of the single crystal particles within the above range can avoid the D50 particle size of the single crystal material being too large, which will lengthen the diffusion path of the sodium ions and deteriorate the rate performance of the battery, and avoid the D50 particle size being too small, which will cause the compaction density of the single crystal material to be low. Specifically, the D50 particle size of the single crystal particles can be 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, etc.; in some embodiments, the D50 particle size of the single crystal material is in the range of 0.5μm-5μm. Among them, controlling the D99 of the single crystal particles within the above range can ensure that the single crystal particles have good dispersibility and avoid excessive agglomeration of primary particles. In some embodiments, the D99 particle size of the single crystal material may be less than or equal to 25 μm, less than or equal to 20 μm, or even less than or equal to 15 μm.

[0053] It should be noted that the D50 particle size and D99 particle size of the above-mentioned single crystal particles can be measured and obtained by statistics based on electron microscope photos containing multiple single crystal particles. Moreover, what is measured is the length of the single crystal particle, that is, its maximum lateral dimension, specifically the distance between the two points with the largest dimension on its cross section. For flaky particles with a hexagonal morphology, its maximum lateral dimension refers to the diameter of the circumscribed circle of the hexagon.

[0054] In the embodiment of the present application, the D50 particle size of the polycrystalline particles is in the range of 1μm-15μm, and the D99 particle size does not exceed 30μm. Among them, controlling the D50 of the polycrystalline particles in the above range can avoid the primary particles constituting the polycrystalline material from being too small, thereby increasing the specific area of ​​the secondary particles, reducing the structural stability, and increasing the probability of interfacial side reactions of the sodium-based transition metal oxide; and avoid excessively increasing the diffusion path of sodium ions in the polycrystalline particles, thereby deteriorating the rate performance of the polycrystalline material. Among them, controlling the D99 of the polycrystalline particles in the above range can avoid the presence of polycrystalline particles with too large a particle size, thereby significantly deteriorating the rate performance of the sodium-based transition metal oxide. Specifically, the D50 particle size of the polycrystalline particles may be 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 14.5 μm, etc. The D99 particle size of the polycrystalline particles may be less than or equal to 25 μm, less than or equal to 20 μm, or even less than or equal to 15 μm, etc.

[0055] In the embodiment of the present application, the compaction density of the sodium positive electrode material at 200 MPa is 2.6-3.5 g / cm 3 , with a specific surface area of ​​0.2-1.5m 2 / g. Based on the control of the XRD characteristics, morphology and size of the primary particles of the aforementioned sodium-based transition metal oxides in the embodiments of the present application, the compaction density and specific surface area of ​​the sodium positive electrode material can reach this condition, which is conducive to ensuring that the sodium battery made from the material has both good cycle stability and high energy density. Specifically, the compaction density of the sodium positive electrode material at 200MPa can be 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, or 3.45 g / cm 3 The specific surface area of ​​the sodium positive electrode material can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1.0, 1.1, 1.2, 1.3 or 1.4 m 2 / g, etc. In some embodiments, the specific surface area is 0.3-1.0m 2 / g.

[0056] Wherein, the above compaction density can be measured by a powder compaction density meter when testing the powdered sodium positive electrode material, and the compaction density read from the device under a pressure of 200MPa. The above specific surface area can be obtained by testing the powdered sodium positive electrode material based on the BET specific surface area test method. In addition, it should be noted that when the sodium positive electrode material also has a coating layer described below in this application, its compaction density and specific surface area can also meet the above ranges.

[0057] In the present application, sodium-based transition metal oxide refers to an oxide containing sodium and transition metal elements. The chemical formula of the sodium-based transition metal oxide may include Na x A y M z O w , wherein A represents a variable valence transition metal element, M represents an element that can be doped / substituted for element A, and M can be selected from one or more of Li (lithium), Al (aluminum), Mg (magnesium), Ca (calcium), Sr (strontium), K (potassium), Sn (tin), Ti (titanium), Zn (zinc), Zr (zirconium), Nb (niobium), Mo (molybdenum), B (boron), etc.; <x≤12,0<y≤12,0≤z≤12,0<w≤12。

[0058] In the embodiment of the present application, A includes one or more of V (vanadium), Fe (iron), Cr (chromium), Mn (manganese), Co (cobalt), Ni (nickel), and Cu (copper), but is not limited thereto.

[0059] In some embodiments of the present application, the sodium positive electrode material 100 may further include a coating layer 20 coated on the surface of the sodium-based transition metal oxide 10. Figure 1B and Figure 1C As shown, the sodium-based positive electrode material 100 at this time can be referred to as including a sodium-based transition metal oxide 10 and a coating layer 20 coated on the sodium-based transition metal oxide 10. When the XRD characteristics of the sodium-based transition metal oxide meet the above conditions, the presence of the coating layer 20 can further improve the air stability and cycle stability of the overall sodium-based positive electrode material 100.

[0060] In the embodiment of the present application, the coating layer 20 can completely cover the surface of the sodium-based transition metal oxide 10, that is, cover the entire surface of the sodium-based transition metal oxide 10 (such as Figure 1B It is also possible to only coat a portion of the surface of the sodium-based transition metal oxide 10 (such as Figure 1C As shown). When the outer surface of the sodium-based transition metal oxide is completely coated by the coating layer 20, it is more effective to prevent the uncoated area of ​​the layered sodium-based transition metal oxide from becoming an invasion site for water, CO2, etc., and better improve the air stability of the core and the stability of the slurry during the slurrying process; during the cycle of the sodium battery, the coating layer with a high degree of coating can also effectively inhibit the side reaction between the core and the electrolyte, thereby ensuring the cycle stability and capacity of the core.

[0061] In the embodiment of the present application, the material of the coating layer 20 may include one or more of oxides, fluorides, and phosphates, but is not limited thereto. For example, the coating layer material as an oxide may be copper oxide (CuO), aluminum oxide (Al2O3), magnesium oxide (MgO), titanium oxide (TiO2), manganese-rich sodium oxide (general formula: Na j MnO2, 0<j≤0.6) and the like; the coating material as fluoride can be specifically one or more of sodium fluoride (NaF), aluminum fluoride (AlF3), magnesium fluoride (MgF2), copper fluoride (CuF2) and the like; the coating material as phosphate can be a polyanionic sodium-containing compound containing phosphate, for example, specifically one or more of NaTi2(PO4)3, NaV2(PO4)2F3, Na3V2(PO4)2F3, Na2CoPO4F, Na2NiPO4F and the like.

[0062] In the embodiment of the present application, the thickness of the coating layer 20 is 0.1nm-100nm. The coating layer 20 of suitable thickness can effectively inhibit the reaction of the inner core layered sodium-based transition metal oxide with water and CO2 in humid air, improve the stability of the inner core material in the air, and help to inhibit its interface side reactions, improve the cycle stability, and will not affect the specific capacity of the inner core material and reduce the energy density of the sodium battery due to the excessive thickness of the coating layer 20. Specifically, the thickness of the coating layer 20 can be 0.2nm, 0.5nm, 1nm, 2nm, 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 80nm, 90nm, 95nm, etc. In some embodiments, the thickness of the coating layer 20 can be 1nm-50nm, and further can be 5nm-20nm.

[0063] The present application also provides a method for preparing the above-mentioned sodium positive electrode material. Specifically, the method for preparing the sodium positive electrode material comprises the following steps:

[0064] (1) mixing a sodium source with other element sources in the sodium-based transition metal oxide to be prepared to obtain a mixed dry material;

[0065] (2) sintering the mixed dry material multiple times to obtain a sodium-based transition metal oxide-containing sodium positive electrode material; wherein, in the multiple sinterings, the holding temperature of each sintering is within the range of 800-1200° C., and the sintered material obtained by each sintering is crushed before the next sintering, so that the X-ray diffraction spectrum of the sodium positive electrode material satisfies: the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and / or the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.0.

[0066] In step (1), the sodium source can be one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, and sodium peroxide.

[0067] In step (1), other element sources in the sodium-based transition metal oxide to be prepared can be provided according to the chemical formula of the sodium-based transition metal oxide to be prepared. In the embodiment of the present application, the other element sources include variable valence transition metal element sources (i.e., A source, A represents a variable valence transition metal element). Among them, A source can be a hydroxide, oxide, salt (such as carbonate, oxalate, acetate, nitrate, sulfate, etc.) of element A. Element A is selected from one or more of V (vanadium), Fe (iron), Cr (chromium), Mn (manganese), Co (cobalt), Ni (nickel), and Cu (copper).

[0068] In some embodiments of the present application, the other element sources may also include an M source. Similarly, the M source may be a hydroxide, an oxide, a salt (such as a carbonate, a nitrate, an oxalate, an acetate, a sulfate, etc.) of the M element. The A element is selected from one or more of V (vanadium), Fe (iron), Cr (chromium), Mn (manganese), Co (cobalt), Ni (nickel), and Cu (copper).

[0069] In step (1), the mixing method may be one or more of ball milling, sand milling, mechanical stirring, mechanical fusion, etc.

[0070] The above step (2) can be said to be: sintering the mixed dry material N times (N≥2), wherein the insulation temperature of the i-th sintering is in the range of 800-1200°C, and the sintered material obtained by the i-th sintering is crushed and then sintered for the i+1th time, where i is any value from 1 to N-1.

[0071] Among them, compared with calcining the mixed dry materials of each element source for preparing the sodium-based transition metal oxide once, the present application adopts the above-mentioned multiple (greater than or equal to twice) sintering process, which can better promote the preferential orientation of the (003) crystal plane of the sodium-based transition metal oxide. In addition, keeping the heat preservation temperature of each sintering in the range of 800-1200°C helps to ensure that the sodium-based transition metal oxide has a high degree of crystallinity; the sintered material obtained after each sintering is crushed to avoid particle aggregation, ensuring that the next sintering can further improve the crystallinity and the preferential orientation of the (003) crystal plane, and ensuring that the primary particle morphology is a hexagonal sheet.

[0072] In the implementation manner of the present application, the crushing process can be specifically carried out in a wall-breaking machine, or a jet mill, etc. Wherein, the crushing process can be carried out after the sintered material obtained by each sintering is cooled to room temperature.

[0073] Specifically, the holding temperature of each sintering can be 800°C, 820°C, 850°C, 870°C, 900°C, 920°C, 950°C, 980°C, 1000°C, 1050°C, 1100°C, 1200°C, etc. Each holding temperature can be the same or different. Among them, the heating rate during each sintering process can be 1-10°C / min, and can further be 1-5°C / min, such as 2°C / min, 3°C / min, 4°C / min, etc. A lower heating rate can avoid the heating rate being too fast and causing greater stress on the interface between the phases. The holding time of each sintering can be 6h-48h, and can further be 6h-20h, such as 7h, 8h, 10h, 12h, 15h, 18h, etc. In addition, the atmosphere of each sintering can be an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere. An oxygen-containing atmosphere is more conducive to the decomposition of various element sources in the form of hydroxides and carbonates, the recombination of various elements, etc.

[0074] In some embodiments of the present application, the multiple sintering is specifically two sinterings (i.e., N=2); and the holding temperature of the second sintering is greater than the holding temperature of the first sintering. Through the two sinterings with increasing sintering temperatures, the crystal defects in the sodium-based transition metal oxide can be more fully repaired, the (003) crystal plane preferential orientation can be better promoted, and the crystal integrity can be improved.

[0075] In some embodiments of the present application, the mixed dry material in step (1) may also contain additives; the additives may include nano-scale oxides, hydroxides or carbonates containing at least one of Mg, B, Mo, Y, Te, In, Ga, W and Ba. The positive-valent elements contained in these additives are different from the positive-valent elements of the other element sources in step (1). The introduction of these additives and the combination of the above-mentioned multiple sintering can reduce the surface energy of the (003) crystal plane of the final sodium positive electrode material, promote the preferential orientation of the (003) crystal plane, suppress the intensity of the diffraction peaks of the (012) and (110) crystal planes from being too strong, and increase the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane / (012) crystal plane.

[0076] In the embodiment of the present application, the mass proportion of the additive in the mixed dry material is 0.1wt%-5.0wt%. This can ensure that the (003) crystal plane of the sodium positive electrode material is appropriately oriented, which can avoid that too little additive is used and the (003) crystal plane cannot be effectively promoted to be preferentially oriented, and that too much additive is used and the impurity content in the obtained sodium positive electrode material is excessive, thereby reducing the specific capacity of the obtained battery.

[0077] The method for preparing the above-mentioned sodium positive electrode material provided in the embodiment of the present application has a simple process, is easy to operate, is suitable for large-scale production, and can produce a sodium positive electrode material having the above-mentioned XRD spectrum characteristics of the present application.

[0078] It should be noted that the above steps (1) and (2) are mainly used to obtain a sodium-based transition metal oxide that meets the XRD spectrum characteristics required by the present application. When the desired sodium positive electrode material also includes a coating layer, the coating layer can be constructed after the above step (2), and / or the coating layer raw material can be introduced into step (1) to form the coating layer through sintering.

[0079] In some embodiments of the present application, a coating layer is constructed after the above step (2). The coating layer can be constructed by mixing a sodium-based transition metal oxide with a coating layer material or a raw material for a synthetic coating layer material. Among them, the coating layer is constructed in a manner including, but not limited to, one or more of a solid phase method, a liquid phase method, and other methods. The solid phase method can be a mechanical stirring method, a solid phase high-energy ball milling method, a mechanical fusion method, etc., and the liquid phase method can be a sol-gel method, a coprecipitation coating method, a hydrothermal / solvothermal coating method, a liquid phase high-energy ball milling method, a coating method, and a spray drying coating method. Generally, when a liquid phase method is used, after the mixing, a heat treatment is required to promote the formation of the coating layer material, enhance the bonding force between it and the sodium-based transition metal oxide, etc. Other methods can be one or more of a chemical vapor deposition method, a physical vapor deposition method (such as a magnetron sputtering method, a plasma sputtering method, an evaporation method), etc.

[0080] The embodiment of the present application also provides a positive electrode plate for a sodium battery, and the positive electrode plate includes the sodium battery positive electrode material described above in the embodiment of the present application.

[0081] See also Figure 2 The positive electrode sheet 200 provided in the embodiment of the present application includes a positive electrode current collector 201 and a positive electrode material layer 202 disposed on the positive electrode current collector 201, and the positive electrode material layer 202 includes the above-mentioned sodium-based positive electrode material 100 in the embodiment of the present application. Among them, the positive electrode material layer 202 may also include a binder, a conductive agent, etc. In some embodiments, the positive electrode material layer 202 may also include other positive electrode active materials different from the sodium-based positive electrode material. The positive electrode material layer 202 is disposed on one side surface or on two opposite sides of the positive electrode current collector 201.

[0082] Among them, positive electrode current collector, conductive agent, binder are conventional choices in the field of sodium batteries. For example, the positive electrode current collector can be aluminum foil, carbon-coated aluminum foil, aluminum-plated polymer film, etc. The binder can specifically include but is not limited to polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyacrylamide (PAM), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and sodium alginate, etc. One or more. The conductive agent can specifically include but is not limited to acetylene black, Ketjen black, Super P conductive carbon black, graphite, graphene, carbon nanotubes, carbon fiber, amorphous carbon, etc. One or more.

[0083] An embodiment of the present application also provides a sodium secondary battery, which includes the above-mentioned positive electrode plate.

[0084] See also Figure 3 The sodium secondary battery 300 provided in one embodiment of the present application includes a positive electrode 301, a negative electrode 302, a diaphragm 303, an electrolyte 304, and corresponding connecting accessories and circuits. The diaphragm 303 is disposed between the positive electrode 301 and the negative electrode 302, and the positive electrode 301, the negative electrode 302, and the diaphragm 303 are immersed in the electrolyte 304. The positive electrode 301 includes the positive electrode sheet 200 described above in the embodiment of the present application, which also correspondingly includes the sodium positive electrode material 100 described above in the embodiment of the present application.

[0085] During the charging process of the sodium secondary battery 300, under the action of the external circuit, the sodium ions (Na + ) escapes from the positive electrode 301 and migrates to the negative electrode 302 through the electrolyte 304 and the diaphragm 303, and at the same time, the electrons flow from the positive electrode to the negative electrode through the external circuit, and the electric energy is stored; the discharge process is opposite to the charging process, the sodium ions escape from the negative electrode 302 and return to the positive electrode 301 through the electrolyte 304 and the diaphragm 303, and at the same time, the electrons migrate from the negative electrode to the positive electrode through the external circuit and release electric energy to the outside. Since the positive electrode of the sodium secondary battery 300 uses the above-mentioned sodium positive electrode material 100, the battery has good cycle stability, rate performance, etc.

[0086] The present application also provides an electric device, which includes the sodium secondary battery provided in the present application. The electric device may include electronic equipment, mobile devices, etc.

[0087] The electronic device may include various consumer electronic products, such as mobile phones, tablet computers, laptop computers, personal digital assistants (PDAs), portable computers, mobile power supplies, wearable devices (such as smart bracelets, smart watches, smart helmets, smart glasses, etc.), home entertainment devices (such as televisions, DVD players, video recorders, camcorders, radios, recorders, stereos, record players, laser record players, etc.), home office equipment (such as scanners, microphones, etc.), home electronic health care equipment, vehicle-mounted equipment, etc. The electronic device may also be a wireless local loop (WLL) station, a device with wireless or wired communication functions (such as communication conversion equipment, lightning arresters, antennas, gateways, remote controls, radars, intercoms, switches, routers, etc.), other processing devices connected to wireless modems, etc., and the embodiments of the present application are not limited to this.

[0088] In some embodiments, see Figure 4 , the electronic device 400 provided in the embodiment of the present application includes a housing 401 and a battery 402 contained in the housing 401, the battery 402 supplies power to the electronic device 400, and the battery 402 includes the sodium secondary battery 300 described above in the embodiment of the present application. The housing 401 may include a front cover assembled on the front side of the terminal and a rear shell assembled on the rear side, and the battery 402 may be fixed on the inside of the rear shell. In some embodiments, the housing 401 may include a front cover assembled on the front side of the terminal and a rear shell assembled on the rear side, and the battery 402 may be fixed on the inside of the rear shell. In addition, a circuit board ( Figure 4 not shown). Figure 4 The electronic device 400 shown may specifically be a mobile phone or the like.

[0089] The mobile device may be any movable device for loading, transporting, assembling, disassembling, security, etc., for example, any vehicle, including but not limited to electric cars, electric trucks, electric motorcycles, electric bicycles, etc. The sodium secondary battery can provide electric energy to drive the mobile device to move.

[0090] See also Figure 5 The embodiment of the present application also provides an energy storage system 500, which includes a battery pack 501 and a battery management system 502 electrically connected to the battery pack 501. The battery pack 501 includes a plurality of sodium secondary batteries 300 provided in the embodiment of the present application. The battery pack 501 may be a module formed by connecting a plurality of sodium secondary batteries 300 in series, in parallel, or in combination thereof. The battery management system 502 may be used to monitor the status information of each sodium secondary battery 300 in the battery pack 501 and control the charge / discharge status thereof.

[0091] The embodiments of the present application are further described below with reference to a plurality of embodiments.

[0092] Example 1

[0093] A preparation method of a sodium positive electrode material, comprising:

[0094] (1) According to the layered oxide material NaNi to be prepared 0.33 Fe 0.33 Mn 0.33 The chemical formula of O2, accurately weigh the sodium source Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2, and add them into a wall breaking machine for mixing to obtain a mixed dry material;

[0095] (2) The mixed dry material is taken out and transferred to a sagger, and then placed in a muffle furnace for a sintering, wherein the first sintering parameters include: heating to a sintering insulation temperature of 800°C at a heating rate of 3°C / min, keeping warm for 10 hours, and naturally cooling to room temperature, and then crushing the obtained first-fired material in a wall breaker, and then sintering for a second time. The process setting is: heating to a sintering insulation temperature of 1000°C at a heating rate of 5°C / min, keeping warm for 15 hours, and then naturally cooling to room temperature, and placing the obtained second-fired material in a grinder for crushing and refining, and passing through a 200-mesh sieve to obtain a sodium positive electrode material, namely NaNi 0.33 Fe 0.33 Mn 0.33 O2.

[0096] Preparation of sodium secondary batteries:

[0097] a) Preparation of positive electrode sheet: The sodium positive electrode material prepared in Example 1 was mixed with the conductive agent Super P and the binder PVDF in a mass ratio of 80:10:10, dissolved in a solvent N-methylpyrrolidone (NMP), and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on a carbon-coated aluminum foil with a scraper, and after drying, rolling and slicing, a positive electrode sheet was obtained.

[0098] b) Assemble the battery: Use the above-mentioned positive electrode sheet as the positive electrode, the metal sodium sheet as the counter electrode, and dissolve NaClO4 in a mixed solvent of propylene carbonate (PC) and fluoroethylene carbonate (FEC) (the volume proportion of FEC is 5%) to obtain a 1M solution as the electrolyte, and assemble it into a button battery in a glove box filled with nitrogen. The electrochemical performance of the button battery can be tested later.

[0099] The XRD spectra of the sodium positive electrode material prepared in Example 1 are summarized in Figure 6In the figure, the (003), (012), and (110) crystal planes of the material have been marked. Figure 6 It can be found through calculation that the I of the sodium positive electrode material in Example 1 (003) / I (012) =3.34>2.7, I (003) / I (110) =6.35>4.0, in addition, I (012) / I (110) =1.90, these results indicate that the material has good (003) crystal plane preferred orientation.

[0100] Figure 7 This is an electron microscope photo of the sodium positive electrode material of Example 1, wherein: Figure 7 The left picture is a scanning electron microscope (SEM) photo, the middle picture is a transmission electron microscope (TEM) photo of the red dotted box area in the left picture, and the right picture is a high-resolution real-time Fourier transform (FFT) photo of the red dotted box area in the middle picture. Figure 7 It can be seen from the left figure that the primary particles of the sodium positive electrode material are hexagonal flaky particles. TEM characterization shows that the crystal plane corresponding to the most exposed plane (i.e., the upper and lower planes of the hexagonal shape) is the (003) crystal plane, which further proves that the material has a good (003) crystal plane preferential orientation. In addition, the length-to-thickness ratio of the above primary particles is about 8.0, with an average length of 6μm and an average thickness of 0.75μm. In addition, the sodium positive electrode material is a single crystal particle with a D50 particle size of 7.2μm and a D99 particle size of 20.5μm.

[0101] Example 2

[0102] A sodium positive electrode material, comprising a layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2, the preparation process is basically the same as that of Example 1, except that the holding temperature of the second sintering is 900°C.

[0103] The XRD spectrum of the sodium positive electrode material prepared in Example 2 is as follows: Figure 8 Based on Figure 8 You can learn: I (003) / I (012) =3.17>2.7, I (003) / I (110) =4.7>4.0, indicating that the material has good (003) crystal plane preferred orientation. In addition, I (012) / I (110) =1.48.

[0104] Fig. 9This is a scanning electron microscope (SEM) photo of the sodium positive electrode material of Example 2. Fig. 9 It can be seen that the ratio of the length to thickness of the primary particles of the sodium positive electrode material is about 3.88, wherein the average length of the primary particles is 3.3 μm and the average thickness is 0.85 μm. In addition, the sodium positive electrode material is a single crystal particle with a D50 particle size of 3.7 μm and a D99 particle size of 15.2 μm.

[0105] Example 3

[0106] A sodium positive electrode material, comprising a layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2, the preparation process is basically the same as that of Example 1, except that the holding temperature of the second sintering is 900°C and the holding time is 12 hours.

[0107] Based on the XRD spectrum of the sodium positive electrode material obtained in Example 3, it can be seen that: (003) / I (012) =3.05>2.7, I (003) / I (110) =5.9>4.0, indicating that the material has good (003) crystal plane preferred orientation. In addition, I (012) / I (110) =1.93.

[0108] Example 4

[0109] A preparation method for a sodium positive electrode material, which is different from that of Example 1 in that 1000 ppm of B2O3 additive is also added to the mixed material in step (1).

[0110] Based on the XRD spectrum of the sodium positive electrode material obtained in Example 4, it can be seen that: (003) / I (012) =3.9>2.7, I (003) / I (110) =6.3>4.0, indicating that the material has good (003) crystal plane preferred orientation. In addition, I (012) / I (110) =1.615.

[0111] Example 5

[0112] A preparation method of a sodium positive electrode material, which is different from that of Example 1 in that: after step (2), it also includes constructing a coating layer. Specifically, it includes: taking the layered oxide material NaNi obtained after secondary sintering 0.33 Fe 0.33 Mn 0.33O2, mixed with 0.65g of magnesium oxide (MgO) powder, sintered in a tube furnace after ball milling, and naturally cooled to room temperature to obtain NaNi coated with MgO on the surface. 0.33 Fe 0.33 Mn 0.33 O2 material.

[0113] Based on the XRD spectrum of the sodium positive electrode material obtained in Example 5, it can be seen that (003) / I (012) =3.08>2.7, I (003) / I (110) =5.3>4.0, indicating that the material has good (003) crystal plane preferred orientation. In addition, I (012) / I (110) =1.72.

[0114] Example 6

[0115] A sodium positive electrode material, a layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2, from the XRD spectrum of the sodium positive electrode material, we can know: (003) / I (012) =3.0>2.7, I (003) / I (110) =3.8<4.0, indicating that the material has good (003) crystal plane preferred orientation. In addition, I (012) / I (110) =1.26.

[0116] Example 7

[0117] A sodium positive electrode material, comprising a layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2, the preparation process is basically the same as that of Example 1, except that the temperature of the second sintering is 1200°C.

[0118] Based on the XRD spectrum of the sodium positive electrode material obtained in Example 7, it can be seen that: (003) / I (012) =3.9>2.7, I (003) / I (110) =8.1>8.0, indicating that the material has excellent (003) crystal plane preferred orientation. In addition, I (012) / I (110) =2.07.

[0119] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0120] Comparative Example 1

[0121] A sodium positive electrode material, comprising a layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2, the preparation process thereof is different from that of Example 1 in that: only one sintering is performed, and the sintering process comprises: heating the temperature to 800°C at a heating rate of 3°C / min, keeping the temperature for 10 hours, and then naturally cooling to room temperature, crushing the obtained sintered material by a pulverizer, and passing through a 200-mesh sieve to obtain a sodium positive electrode material.

[0122] The XRD spectra of the sodium positive electrode material prepared in Comparative Example 1 are also summarized in Figure 6 Based on Figure 6 After calculation, it can be found that the I of the sodium positive electrode material in Comparative Example 1 (003) / I (012) =2.61<2.7, I (003) / I (110) =3.89<4.0, which indicates that the material does not have a good (003) crystal plane preferred orientation.

[0123] In order to measure the air stability of each sodium positive electrode material of the present application, the sodium positive electrode materials of other embodiments and comparative examples were prepared into positive electrode slurries according to the method described in Example 1, and each positive electrode slurry was placed in an environment with a relative humidity of 10%, and the time required for the slurry to change from a flowing state to a non-flowing state was tested, that is, the gelation time of the slurry was recorded. The results are summarized in the following Table 1.

[0124] In order to measure the cycle stability of the sodium positive electrode material of the embodiment of the present application, the sodium positive electrode materials of other embodiments and comparative examples were prepared into positive electrode sheets and assembled into sodium button batteries according to the method described in Example 1. The first cycle charging capacity of each sodium button battery at 0.1C and the capacity retention rate after 30 cycles at 0.5C were tested, where 1C = 150mA / g and the voltage window was 2-4.1V.

[0125] Table 1

[0126]

[0127] From the comparison between Example 1 and Comparative Example 1 in Table 1, it can be seen that compared with Comparative Example 1 whose XRD spectrum characteristics do not meet the definition of this application, the gelation time of the sodium positive electrode material provided in Example 1 of the present application after being placed in a humid environment is significantly longer, indicating that its air stability is significantly improved, and the gelation time after being placed in a humid environment is significantly longer. At the same time, the capacity retention rate of the sodium button battery made of the sodium positive electrode material of Example 1 of the present application measured under the same conditions is also higher than that of Comparative Example 1, which can be increased to 94.1%, and the first charge capacity of the battery has not decreased.

[0128] Similarly, the sodium positive electrode materials provided in other embodiments of the present application can also take into account good air stability and cycle stability. (003) / I (012) >2.7 and I (003) / I (110) The air stability and cycle stability of the sodium positive electrode material of Example 6 with a value of >4.0 are slightly worse than those of the other examples, but still better than those of Comparative Example 1. (003) The crystal plane orientation is higher (I (003) / I (110) >8.0) has higher air stability, but its kinetic performance (reflected by the first charge capacity) is lower than that of Examples 1-3, but the decline is not obvious, and the first charge capacity of the battery is still within the high range recognized by the industry.

[0129] The above only expresses several exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.

[0130] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.

[0131] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0132] In this application, "at least one" means one or more, and "more than one" means greater than or equal to two. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

Claims

1. A sodium positive electrode material, characterized in that: The sodium-based positive electrode material comprises a sodium-based transition metal oxide, and the X-ray diffraction spectrum of the sodium-based positive electrode material satisfies: The ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and / or The ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.

0.

2. The sodium positive electrode material according to claim 1, characterized in that The ratio of the diffraction peak intensity of the (012) crystal plane to the (110) crystal plane is in the range of 1.0-3.

0.

3. The sodium positive electrode material according to claim 1 or 2, characterized in that The ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is in the range of 2.7-6.

0.

4. The sodium positive electrode material according to claim 3, characterized in that The ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is in the range of 3.0-5.

0.

5. The sodium positive electrode material according to claim 4, characterized in that The ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is in the range of 3.01-4.

0.

6. The sodium positive electrode material according to any one of claims 1 to 5, characterized in that The ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is in the range of 4.0-8.

0.

7. The sodium positive electrode material according to claim 6, characterized in that The ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is in the range of 4.1-7.

0.

8. The sodium positive electrode material according to any one of claims 1 to 7, characterized in that The sodium-based transition metal oxide includes single crystal particles and / or polycrystalline particles; wherein the single crystal particles are primary particles, and the polycrystalline particles are secondary particles composed of a plurality of the primary particles.

9. The sodium positive electrode material according to claim 8, characterized in that The primary particles are hexagonal flake particles, and the ratio of the length to the thickness of the primary particles is in the range of 1.5-8.

0.

10. The sodium positive electrode material according to claim 9, characterized in that The thickness of the primary particles is in the range of 0.04 μm to 6 μm.

11. The sodium positive electrode material according to any one of claims 8 to 10, characterized in that: The D50 particle size of the single crystal particles is in the range of 0.5 μm-12 μm, and the D99 particle size is no more than 30 μm.

12. The sodium positive electrode material according to any one of claims 8 to 10, characterized in that: The morphology of the polycrystalline particles includes one or more of spherical, ellipsoidal, and flower-like shapes.

13. The sodium positive electrode material according to claim 12, characterized in that: The D50 particle size of the polycrystalline particles is in the range of 1 μm-15 μm, and the D99 particle size is no more than 30 μm.

14. The sodium positive electrode material according to any one of claims 1 to 13, characterized in that: The chemical formula of the sodium-based transition metal oxide includes Na x A y M z O w , wherein A is a variable valence transition metal element, and M is selected from one or more of Li, Al, Mg, Ca, Sr, K, Sn, Ti, Zn, Zr, Nb, Mo, and B; <x≤12,0<y≤12,0≤z≤12,0<w≤12。 15. The sodium positive electrode material according to claim 14, characterized in that The A includes one or more of V, Fe, Cr, Mn, Co, Ni, and Cu.

16. The sodium positive electrode material according to any one of claims 1 to 14, characterized in that: The sodium positive electrode material also includes a coating layer coated on the surface of the sodium-based transition metal oxide; wherein the material of the coating layer includes one or more of oxides, fluorides, and phosphates.

17. The sodium positive electrode material according to claim 16, characterized in that The coating layer has a thickness of 0.1 nm to 100 nm.

18. The sodium positive electrode material according to claim 16 or 17, characterized in that: The coating layer completely covers the surface of the sodium-based transition metal oxide.

19. The sodium positive electrode material according to any one of claims 1 to 18, characterized in that: The compaction density of the sodium positive electrode material at 200 MPa is 2.6-3.5 g / cm 3 , with a specific surface area of ​​0.2-1.5m 2 / g.

20. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes the sodium battery positive electrode material according to any one of claims 1 to 19.

21. A sodium secondary battery, characterized in that: The sodium secondary battery comprises the positive electrode sheet and the negative electrode sheet as claimed in claim 20.

22. An electrical equipment, characterized in that: The electrical equipment includes the sodium secondary battery as claimed in claim 21.

23. The electrical equipment according to claim 22, characterized in that: The power-consuming device includes one or more of an electronic device and a mobile device.

24. The electrical equipment according to claim 23, characterized in that: The electronic device includes a housing and the sodium secondary battery accommodated in the housing, and the sodium secondary battery is used to power the electronic device.

25. An energy storage system, characterized in that: The energy storage system includes a battery pack and a battery management system electrically connected to the battery pack, wherein the battery pack includes a plurality of the sodium secondary batteries as claimed in claim 21.

26. A method for preparing a sodium positive electrode material, characterized in that: The following steps are involved: mixing a sodium source with other element sources in the sodium-based transition metal oxide to be prepared to obtain a mixed dry material; The mixed dry material is sintered multiple times to obtain a sodium-based transition metal oxide-containing sodium-based positive electrode material; wherein, in the multiple sinterings, the insulation temperature of each sintering is within the range of 800-1200° C., and the sintered material obtained by each sintering is crushed before the next sintering, so that the X-ray diffraction spectrum of the sodium-based positive electrode material satisfies: the ratio of the diffraction peak intensity of the (003) crystal plane to the (012) crystal plane is greater than or equal to 2.7, and / or the ratio of the diffraction peak intensity of the (003) crystal plane to the (110) crystal plane is greater than or equal to 4.0.